Authors (The Biblical archaeology review, 2024)
Aaron A. Burke (Book Review: The Bible Among Ruins) is Professor of the Archaeology of Ancient Israel and the Levant, and the Kershaw Chair in the Archaeology of the Ancient Eastern Mediterranean in the Department of Near Eastern Languages and Cultures at the University of California, Los Angeles. Katia Cytryn (Milestone: Donald Whitcomb (1944-2024)) is […]